Kerjasama Hindu-Islam Dalam Hubungan Antar Agama di Desa Kiluan Lampung - Zarkasi, Ahmad; Ruslan, Idrus; Rosana, Ellya; Kalsum, Afif Umi (Universitas Islam Negeri Raden Intan Lampung, 2020)
The actualization of the paradigm of cooperation between religious communities is the most important agenda for activists of inter-religious harmony, especially religious believers themselves. Especially for the people who live in a multi-religious area, because there is no religion teaches hatred in order to harmony between religious communities must be cared for and maintained well. In relations between religious communities, this is need for collective action in facing the challenges of the future of humanity, because of considering the reality of Indonesia which adheres to absolute multiculturalism. This research used field research to raise a phenomenon of cooperation between religious community in the village of Kiluan by used descriptive analysis techniques and direct interviews. The results of this study indicate that the cooperation carried out by the community is associative, namely the cooperative relationship that exists in every aspect of social life and also supported by government and local religious leader. In conclusion, if all the stake holders well cooperate in every social life, the paradigm of cooperation between religious communities is well actualized and fully tolerated.